Heat transfer member and method for manufacturing same

By forming an oxide layer with a specific shape on the surface of the base material of the heat transfer component, the problem that the refrigerant is difficult to boil after repeated boiling and long-term immersion is solved, the effect of maintaining the boiling of the refrigerant for a long time is achieved, and the cooling efficiency is improved.

CN119343484APending Publication Date: 2025-01-21KYUSHU UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380048715.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-08-03
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

After repeated boiling and long-term impregnation of the existing boiling heat transfer surface, the refrigerant is difficult to boil, resulting in a decrease in cooling efficiency.

Method used

By forming an oxide layer with a specific shape on the surface of the base material of the heat transfer member, the oxide layer has a plurality of pores, the opening diameter of the first part is 5 nm or more and 70 nm or less, the pore diameter of the second part is larger than the first part, and is similar to the opening diameter of the first part. The first part is connected, and the average depth of the second part is above 600nm and below 20μm.

Benefits of technology

When in contact with superheated refrigerant, this structure promotes the vaporization of the refrigerant and generates a large number of bubbles. It also inhibits the entry of liquid refrigerant through the design of pores, maintains the gas in the pores, and maintains the boiling effect of the refrigerant for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343484A_ABST
    Figure CN119343484A_ABST
Patent Text Reader

Abstract

A heat transfer member (1) is provided with: a base material (2) comprising a metal or an inorganic compound containing a metal element; and an oxide layer (3) formed on the base material (2) and comprising an oxide of a metal element contained in the base material (2). The oxide layer (3) has a plurality of pores (31) provided with: a first portion (312) having openings (311) in the surface of the heat transfer member (1), the openings (311) having an average opening diameter of 5 nm to 70 nm (inclusive); and a second portion (313) having an average pore diameter larger than an average opening diameter of the first portion (312) and connected to the first portion (312). The average depth of the second portion (313) is 600 nm or more and 20 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat transfer component and a method for manufacturing the same. Background Art

[0002] Cooling systems that utilize the phase change of refrigerants, such as boiling coolers, are sometimes installed in equipment that generates a large amount of heat, such as air conditioners, coolers, boilers, and heat engine generators. In recent years, such cooling systems are sometimes also used to cool semiconductor components with high heat density, electronic equipment for data centers, and the like.

[0003] A cooling system utilizing boiling of a refrigerant has a heat transfer member having a heat receiving surface configured to be in thermal contact with a device to be cooled and a heat dissipation surface configured to be in contact with the refrigerant. This cooling system is configured to efficiently cool the device to be cooled by boiling the refrigerant in contact with the heat dissipation surface of the heat transfer member. In addition, as a technology for promoting boiling of the refrigerant, for example, Patent Document 1 describes a boiling heat transfer surface characterized in that the surface where liquid boiling occurs has a surface roughness with densely packed asperities of 10 nm to 1000 nm in height.

[0004] Prior Art Literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2002-228389 Summary of the invention Technical problem to be solved by the invention As mentioned above, the cooling system using boiling refrigerant can efficiently cool the equipment to be cooled by boiling the refrigerant in contact with the heat dissipation surface of the heat transfer component. However, the boiling heat transfer surface described in Patent Document 1, for example, makes it difficult for the refrigerant to boil when the refrigerant is repeatedly boiled or immersed in the refrigerant for a long time, and there is a tendency for the superheat of the refrigerant near the heat dissipation surface to increase when boiling begins. In this way, if the refrigerant in contact with the heat dissipation surface becomes difficult to boil, the amount of heat transferred from the heat dissipation surface to the refrigerant decreases, which may cause the temperature of the equipment to be cooled to rise.

[0005] The present invention has been made in view of the above background, and an object of the present invention is to provide a heat transfer member capable of maintaining the effect of promoting boiling of a refrigerant for a long period of time, and a method for manufacturing the same.

[0006] Technical solutions for solving technical problems One embodiment of the present invention is a heat transfer member including: a base material composed of a metal or an inorganic compound containing a metal element; and an oxide layer composed of an oxide of a metal element contained in the base material and formed on the base material, The oxide layer has a plurality of pores, the plurality of pores comprising: a first portion having an opening on the surface of the heat transfer member, wherein the average opening diameter of the opening is greater than or equal to 5 nm and less than or equal to 70 nm; and a second portion having an average pore diameter greater than the average opening diameter of the first portion and connected to the first portion, The average depth of the second portion is 600 nm or more and 20 μ m or less.

[0007] In addition, another aspect of the present invention is a method for manufacturing the heat transfer member of the above aspect, comprising the following steps: By performing an anodic oxidation treatment on the base material under a first treatment condition, an oxide layer is formed on the surface of the base material, wherein the oxide layer has a plurality of pores having an average opening diameter of 5 nm or more and 70 nm or less; Then, the base material is anodized under a second treatment condition different from the first treatment condition to grow a part of the plurality of pores, thereby forming the second portion connected to the first portion.

[0008] Effects of the Invention The oxide layer of the heat transfer member is provided with a plurality of pores having the first part and the second part. The pores having such a shape promote the vaporization of the refrigerant when in contact with the refrigerant in the superheated state, and can generate a large number of bubbles. In addition, the first part of the pores has an opening with a relatively small opening diameter, so that the growing bubbles can be quickly separated from the heat transfer member.

[0009] In addition, by making the average opening diameter of the first portion of the pores smaller than the average pore diameter of the second portion, it is possible to suppress the refrigerant in the liquid phase from entering the pores. In addition, by setting the average depth of the second portion of the pores to the specific range, it is possible to maintain a sufficient amount of gas in the pores, for example, even in the case of repeated boiling of the refrigerant or long-term immersion in the refrigerant. The gas maintained in the pores helps to generate bubble nuclei when the temperature of the refrigerant rises, so by maintaining the gas in the pores, it is possible to promote the generation of bubbles from the refrigerant, that is, promote the boiling of the refrigerant. Therefore, even in the case of repeated boiling of the refrigerant or long-term immersion in the refrigerant, the heat transfer member can promote the boiling of the refrigerant and boil the refrigerant during a period when the superheat of the refrigerant is relatively low.

[0010] As a result of the above, the heat transfer member can maintain the effect of promoting boiling of the refrigerant for a long period of time.

[0011] In addition, in the manufacturing method of the above-described manner, an oxide layer is formed on the surface of the base material by performing anodic oxidation treatment in two stages, and pores having a first part and a second part are formed in the oxide layer. Thus, by using an electrochemical method such as anodic oxidation treatment, pores having the specific shape can be easily formed.

[0012] As described above, according to the above-described manner, a heat transfer member capable of maintaining the effect of promoting the boiling of the refrigerant for a long time and a manufacturing method thereof can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a partial cross-sectional view showing the main part of the heat transfer member in the embodiment.

[0014] Figure 2 It is a partial cross-sectional view showing the main part of the heat transfer member after the first anodic oxidation treatment in the embodiment.

[0015] Figure 3 It is a perspective view of the heat transfer member in the experimental example.

[0016] Figure 4 It is an electron micrograph of the surface of the oxide layer of the test body S1 in the experimental example.

[0017] Figure 5 It is an electron micrograph of the cross-section of the oxide layer of the test body S1 in the experimental example.

[0018] Figure 6 It is an explanatory diagram schematically showing an experimental apparatus used for a subcooled pool boiling experiment in the experimental example.

[0019] Figure 7 It is an explanatory diagram showing an example of a boiling curve in the experimental example. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0020] (Heat Transfer Member) The heat transfer component, for example, has a heat receiving surface configured to be in thermal contact with the equipment to be cooled and a heat dissipation surface configured to be in contact with the refrigerant. The base material of the heat transfer component is composed of a metal or an inorganic compound containing a metal element. As the metal constituting the base material, for example, aluminum, aluminum alloy, titanium, titanium alloy and other metals that can form a porous oxide film by anodizing can be used. In addition, as the inorganic compound constituting the base material, for example, indium phosphide (InP) and other metals that can form a porous oxide film by anodizing can be used. From the viewpoint of improving the cooling performance of the heat transfer component and reducing the material cost, the base material of the heat transfer component is preferably any one of aluminum, aluminum alloy, titanium or titanium alloy, and more preferably any one of aluminum or aluminum alloy.

[0021] The chemical composition of the aluminum used as the base material of the heat transfer member is not particularly limited, and for example, 1000 series aluminum can be used as the base material. In addition, the chemical composition of the aluminum alloy used as the base material of the heat transfer member is not particularly limited, and for example, 2000 series alloy, 3000 series alloy, 4000 series alloy, 5000 series alloy, 6000 series alloy, and 7000 series alloy can be used as the base material. From the viewpoint of thermal conductivity, the base material of the heat transfer member is preferably composed of 1000 series aluminum or 6000 series alloy.

[0022] An oxide layer composed of an oxide of a metal element contained in the base material is provided on the base material. For example, when the base material is composed of aluminum or an aluminum alloy, the oxide layer is composed of aluminum oxide. In addition, when the base material is composed of titanium or a titanium alloy, the oxide layer is composed of titanium dioxide. The oxide layer can be provided on the entire surface of the heat transfer member or on a partial area of ​​the surface. From the viewpoint of efficiently performing heat exchange with the refrigerant, the oxide layer is preferably provided on at least the heat dissipation surface of the heat transfer member.

[0023] A plurality of pores are formed in the oxide layer, and the plurality of pores include a first portion having an opening on the surface of the heat transfer member and a second portion connected to the first portion. In addition, the average opening diameter of the opening in the first portion is greater than 5 nm and less than 70 nm, and the average pore diameter of the second portion is greater than the average opening diameter of the first portion. It should be noted that a pore whose opening diameter is smaller than the pore diameter inside the pore is sometimes referred to as a concave cavity.

[0024] The pores having an average opening diameter of 5 nm or more in the first part can suppress the excessive growth of bubbles generated by the gasification of the refrigerant, and make the bubbles detach from the heat transfer member when the size of the bubbles is relatively small. Therefore, the heat transfer member can efficiently cool the device to be cooled. From the viewpoint of further improving the effect of this effect, the average opening diameter of the first part of the pores is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more.

[0025] In addition, the pores having an average opening diameter of 70 nm or less in the first part can inhibit the liquid refrigerant from entering the inside from the outside of the pores. As a result, it is easy to retain gas inside the pores, and the effect of promoting the boiling of the refrigerant can be maintained for a long time. From the viewpoint of more reliably obtaining this effect, the average opening diameter of the first part of the pores is preferably 60 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less.

[0026] From the viewpoint of further improving the effect of promoting the separation of bubbles from the heat transfer component and more effectively inhibiting the liquid refrigerant from entering the interior of the pores, the average opening diameter of the first part of the pores is preferably greater than 10 nm and less than 60 nm, more preferably greater than 15 nm and less than 50 nm, and further preferably greater than 20 nm and less than 40 nm.

[0027] The calculation method of the average opening diameter of the first part is as follows. First, the surface of the oxide layer is observed using an electron microscope to obtain an electron microscope image of the surface of the oxide layer. Then, 10 or more pores are randomly selected from the plurality of pores present in the electron microscope image, and the equivalent circle diameter of the opening of each pore, that is, the diameter of a circle having an area equal to the area of ​​the opening, is measured. The arithmetic mean of the equivalent circle diameters of the first part obtained in this way is set as the average opening diameter of the first part.

[0028] The average depth of the first part of the pores is preferably 100 nm or more and 2 μ m or less, more preferably 150 nm or more and 1 μ In this case, the liquid refrigerant can be more effectively prevented from entering the pores, and the gas in the pores can be more easily guided to the outside of the pores, thereby promoting the formation of bubbles.

[0029] The method for calculating the average depth of the first part of the pores is as follows. First, a section roughly parallel to the thickness direction of the oxide layer is exposed by breaking the oxide layer of the heat transfer component, cutting the heat transfer component, or embedding the heat transfer component in a resin and then mechanically grinding it. The section is observed using an electron microscope to obtain an electron microscope image. Then, three or more pores are randomly selected from the multiple pores existing in the electron microscope image, and the depth of the part in the first part of each pore where the pore diameter is roughly the same (that is, the length of the part where the pore diameter in the extension direction of the first part is roughly the same) is measured. The arithmetic mean of the depths of the first part obtained in this way is set as the average depth of the first part.

[0030] The second part of the pore is connected to the first part and extends from the front end of the first part toward the base material. The average pore size of the second part is larger than the average opening diameter of the first part. The average pore size of the second part is preferably greater than 70nm and less than 1000nm. In this case, the volume of the second part can be further increased. As a result, the amount of gas retained in the second part can be further increased, and the effect of promoting the boiling of the refrigerant can be maintained for a longer period of time. From the viewpoint of further improving the effect of this action, the average pore size of the second part is more preferably greater than 90nm and less than 800nm, more preferably greater than 100nm and less than 600nm, and particularly preferably greater than 110nm and less than 400nm.

[0031] The method for calculating the average pore size of the second part of the pores is as follows. First, a section roughly parallel to the thickness direction of the oxide layer is exposed by breaking the oxide layer of the heat transfer component, cutting the heat transfer component, or embedding the heat transfer component in a resin and then mechanically grinding it. The section is observed using an electron microscope to obtain an electron microscope image. Then, four or more pores are randomly selected from the multiple pores existing in the electron microscope image, and the pore size of the central part of the second part in the depth direction of the second part of each pore is measured. The arithmetic mean of the pore size of the second part obtained in this way is set as the average pore size of the second part.

[0032] The average depth of the second portion is 600 nm or more and 20 μ m or less. By setting the average depth of the second part to be 600 nm or more, the volume of the second part can be increased, and a sufficient amount of gas can be maintained in the pores. As a result, the effect of promoting the boiling of the refrigerant can be maintained for a long time. From the viewpoint of further improving the effect of this action, the average depth of the second part is preferably 800 nm or more, and more preferably 1 μ m or more.

[0033] In addition, the average depth of the second part is preferably more than 3 times the average depth of the first part. In this case, the volume of the second part can be further increased, and the amount of gas that can be retained in the pores can be further increased. As a result, the effect of promoting the boiling of the refrigerant can be maintained for a longer period of time. It should be noted that the upper limit of the ratio of the average depth of the second part to the average depth of the first part is, for example, 300.

[0034] The method for calculating the average depth of the second part of the pores is as follows. First, a section roughly parallel to the thickness direction of the oxide layer is exposed by breaking the oxide layer of the heat transfer component, cutting the heat transfer component, or embedding the heat transfer component in a resin and then mechanically grinding it. The section is observed using an electron microscope to obtain an electron microscope image. Then, three or more pores are randomly selected from the multiple pores existing in the electron microscope image, and the depth from the bottom of each pore to the lower end of the first part, that is, to the lower end of the part where the pore diameter is roughly equal to the opening diameter (that is, the length from the bottom of the pore to the lower end of the first part) is measured. The arithmetic mean of the depths of the second part obtained in this way is set as the average depth of the second part.

[0035] In the oxide layer, in addition to the pores having the first part and the second part, i.e., the concave cavities, pores having shapes other than the specific shape can also be formed. For example, in the case where the oxide layer is formed by anodizing the base material in two stages as described above, second pores having the same opening diameter and depth as the first part can be formed on the surface of the oxide layer. Such second pores have the effect of increasing the contact area between the oxide layer and the refrigerant and promoting the generation of bubbles. Therefore, in addition to providing the pores having the specific shape in the oxide layer, by providing the second pores having an opening on the surface of the heat transfer component and the average opening diameter of the opening being greater than 5nm and less than 70nm, the cooling performance of the heat transfer component can be further improved.

[0036] The shape of the heat transfer member is not particularly limited. The heat transfer member may be configured as, for example, a heat pipe, a radiator, a heat exchange fin, or the like.

[0037] (Cooling system) The cooling system including the heat transfer member includes, for example, a heat transfer member and a refrigerant in contact with the oxide layer of the heat transfer member. For example, when the heat transfer member is a tube, by providing an oxide layer on the inner surface of the tube and sealing a refrigerant inside the tube, a heat pipe as a cooling system can be formed. In addition, when the heat transfer member is a plate-shaped radiator, for example, a heat generating element such as a semiconductor element is mounted on one surface of the heat transfer member, and an oxide layer is provided on the other surface so that the oxide layer is in contact with the refrigerant.

[0038] As refrigerants, hydrocarbons such as ethanol, propanol, and isopropanol, fluorine compounds such as hydrofluorocarbons (HFCs), hydrochlorofluorocarbons (HCFCs), hydrofluoroolefins (HFOs), and hydrofluoroethers (HFEs), carbon dioxide, and ammonia can be used. As refrigerants, it is preferred to use refrigerants with a boiling point of less than 100°C, and ethanol and hydrofluoroethers are particularly preferred. By using such refrigerants, the refrigerant can be boiled before the temperature of semiconductor elements and electronic equipment rises excessively and malfunctions, thereby suppressing further increases in the temperature of semiconductor elements and electronic equipment. Therefore, a cooling system with a refrigerant with a boiling point of less than 100°C is suitable for cooling semiconductor elements and electronic equipment.

[0039] The cooling system is preferably configured such that the superheat of the refrigerant on the oxide layer when the refrigerant starts to boil is 20 K or less, more preferably 18 K or less, and further preferably 16 K or less. In this case, the refrigerant in contact with the oxide layer boils more easily, and the equipment to be cooled can be efficiently cooled before the temperature of the equipment rises excessively.

[0040] (Method for manufacturing heat transfer member) When manufacturing the heat transfer component, first, an anodizing treatment is performed on the base material under a first treatment condition, thereby forming an oxide layer having a plurality of pores with an average opening diameter of 5 nm or more and 70 nm or less on the surface of the base material. Then, an anodizing treatment is performed on the base material under a second treatment condition different from the first treatment condition, so that a part of the plurality of pores grows, thereby forming a second part connected to the first part. It should be noted that, hereinafter, the first stage of the anodizing treatment in the two-stage anodizing treatment is referred to as the first anodizing treatment, and the second stage of the anodizing treatment is referred to as the second anodizing treatment.

[0041] In the first anodizing treatment, an oxide layer is formed on the surface of the base material, and a portion corresponding to the first portion of the pore is formed in the oxide layer. In the first anodizing treatment, the oxide layer can be formed by various methods such as constant voltage direct current electrolysis, constant current direct current electrolysis, and pulse electrolysis. In the first anodizing treatment, the oxide layer is preferably formed on the surface of the base material by constant voltage direct current electrolysis or pulse electrolysis. In this case, pores having a desired shape can be easily formed.

[0042] The treatment conditions in the first anodizing treatment, i.e., the first treatment conditions, can be appropriately set according to the material of the base material and the electrolysis method. For example, when an oxide layer is formed on the surface of a base material composed of aluminum or an aluminum alloy by constant voltage direct current electrolysis, an acidic electrolyte containing electrolytes such as sulfuric acid and phosphoric acid can be used, or an alkaline electrolyte containing electrolytes such as sodium metaborate can be used. In this case, the applied voltage can be appropriately set in the range of 10V to 70V, for example. In addition, the temperature of the electrolyte can be appropriately set in the range of 0°C to 40°C, for example.

[0043] When an oxide layer is formed on the surface of a base material composed of aluminum or an aluminum alloy by constant current direct current electrolysis, an acidic electrolyte containing an electrolyte such as sulfuric acid or phosphoric acid is used, and a current density of, for example, 1 mA / cm 2 ~20mA / cm 2 , the temperature of the electrolyte can be set to, for example, 0°C to 40°C. In addition, when an oxide layer is formed on the surface of a base material composed of aluminum or an aluminum alloy by pulse electrolysis, an acidic electrolyte containing an electrolyte such as sulfuric acid or phosphoric acid is used, the applied voltage is set to 10V to 70V, the duty cycle is set to 0.2 to 0.8, and the temperature of the electrolyte is set to 0°C to 40°C.

[0044] In addition, when an oxide layer is formed on the surface of a base material composed of aluminum or an aluminum alloy, an AC aluminum anti-corrosion treatment using an alkaline electrolyte can also be performed. In this case, as the alkaline electrolyte, for example, an aqueous solution containing phosphates such as sodium phosphate, sodium hydrogen phosphate, sodium pyrophosphate, potassium pyrophosphate, and sodium metaphosphate; alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; carbonates such as sodium carbonate, sodium hydrogen carbonate, and potassium carbonate; ammonium hydroxide; or a mixture thereof as an electrolyte can be used.

[0045] The second anodizing treatment can be continued after the first anodizing treatment. In addition, the second anodizing treatment can also be carried out after the first anodizing treatment is completed and other treatments are performed. In the second anodizing treatment, a part of the pores formed in the oxide layer in the first anodizing treatment grows to form a second part. More specifically, the front end of the part formed in the first anodizing treatment in the pore forms a part with a pore diameter larger than that part. Thus, the pores formed in the oxide layer in the first anodizing treatment become the first part or the second pores in the concave cavity, and the part grown from the front end of the first part in the second anodizing treatment becomes the second part. In the second anodizing treatment, it is preferred to form an oxide layer on the surface of the base material by constant voltage direct current electrolysis or pulse electrolysis. In this case, pores having a desired shape can be easily formed.

[0046] The treatment conditions in the second anodizing treatment, i.e., the second treatment conditions, can be appropriately set according to the material of the base material and the electrolysis method. For example, in the case where the second anodizing treatment is performed by constant voltage direct current electrolysis, an acidic electrolyte containing electrolytes such as sulfuric acid and phosphoric acid can be used, or an alkaline electrolyte containing electrolytes such as sodium metaborate can be used. In this case, the applied voltage can be appropriately set in the range of 100V to 300V, for example. In addition, the temperature of the electrolyte can be appropriately set in the range of 0°C to 40°C, for example. In the case where the second anodizing treatment is performed by constant voltage direct current electrolysis, the applied voltage in the second treatment condition is preferably higher than the applied voltage in the first treatment condition. As a result, the pore size of the portion formed by the second anodizing treatment can be more reliably increased, making it easier to form the second portion.

[0047] In the second anodizing treatment, the second porous layer can also be formed by pulse electrolysis or AC alumite treatment using an alkaline electrolyte.

[0048] When the first anodizing treatment and the second anodizing treatment are performed continuously, the applied voltage in the first anodizing treatment can also be switched to the applied voltage in the second anodizing treatment, but it is preferred that the applied voltage in the first anodizing treatment be continuously changed to the applied voltage in the second anodizing treatment over a certain period of time. By slowly changing the applied voltage in the first anodizing treatment and performing the second anodizing treatment, the uneven growth of the oxide layer caused by the rapid application of a high voltage can be suppressed.

[0049] Example (Example) Reference Figure 1 as well as Figure 2 The embodiment of the heat transfer member is described below. Figure 1 As shown, the heat transfer member 1 of this example has: a base material 2, which is composed of a metal or an inorganic compound containing a metal element; and an oxide layer 3, which is composed of an oxide of a metal element contained in the base material 2 and is formed on the base material 2. The oxide layer 3 has a plurality of pores 31, and the plurality of pores 31 include: a first portion 312, which has an opening 311 on the surface of the heat transfer member 1, and the average opening diameter of the opening 311 is greater than 5nm and less than 70nm; and a second portion 313, whose average pore diameter is greater than the average opening diameter of the first portion 312, and is connected to the first portion 312. In addition, the average depth of the second portion 313 of the pore 31 is greater than 600nm and less than 20 μ m or less.

[0050] The base material 2 of the heat transfer member 1 of this example is made of aluminum or aluminum alloy. The oxide layer 3 is made of aluminum oxide and includes: a barrier layer 32, which is stacked on the base material 2 and does not have pores 31; a first porous layer 33, which is exposed on the outermost surface of the heat transfer member 1 and has a first portion 312 of the pores 31; and a second porous layer 34, which is interposed between the barrier layer 32 and the first porous layer 33 and has a second portion 313 of the pores 31.

[0051] The first part 312 of the pore 31 in the first porous layer 33 extends in a direction substantially parallel to the thickness direction of the oxide layer 3 and has a substantially uniform pore diameter in the entire depth direction. In addition, the first part 312 of the pore 31 in the first porous layer 33 is connected to any second part 313.

[0052] In addition, the first porous layer 33 has a plurality of second pores 35 that are not connected to the second portion 313 in addition to the first portion 312 of the pores 31. The second pores 35 have openings 351 on the surface of the heat transfer member 1. In addition, the second pores 35 extend in a direction substantially parallel to the thickness direction of the oxide layer 3 and have a substantially uniform pore diameter in the entire depth direction. The average opening diameter and average depth of the second pores 35 are the same as those of the first portion 312 of the pores 31.

[0053] The second portion 313 of the pore 31 in the second porous layer 34 is connected to any of the first portions 312 of the pore 31 in the first porous layer 33. The second portion 313 extends in substantially parallel directions and has a substantially uniform pore diameter throughout the depth direction.

[0054] The manufacturing method of the heat transfer component 1 of this example is as follows. First, after the base material 2 composed of aluminum or aluminum alloy is formed into the desired shape, a first anodizing treatment is performed. The electrolysis method in the first anodizing treatment is set to a constant voltage DC electrolysis method or a constant current DC electrolysis method, and the electrolyte is set to an acidic electrolyte containing electrolytes such as sulfuric acid and phosphoric acid. When the first anodizing treatment is performed by a constant voltage DC electrolysis method, for example, the applied voltage is set to 20V, and the temperature of the electrolyte is set to 0°C~40°C. By performing the first anodizing treatment under such conditions, it is possible to Figure 2 As shown in FIG. 1 , an oxide layer 30 is formed on the base material 2. The oxide layer 30 thus formed is composed of a barrier layer 32 stacked on the base material 2 and a first porous layer 33 stacked on the barrier layer 32, and pores 36 having openings 361 with an average opening diameter of 5 nm or more and 70 nm or less are formed in the first porous layer 33.

[0055] After the first anodizing treatment is completed, the second anodizing treatment is performed. The electrolysis method in the second anodizing treatment is set to a constant voltage direct current electrolysis method, and the electrolyte is set to an acidic electrolyte containing phosphoric acid as an electrolyte. In addition, in the second anodizing treatment, the applied voltage is increased to 120V in, for example, 2.5 minutes from the moment the first anodizing treatment is completed, and the applied voltage is maintained. The temperature of the electrolyte in the second anodizing treatment is set to 10°C. By performing the second anodizing treatment under such conditions, it is possible to Figure 2 The oxide layer 30 grows in the reactor.

[0056] In the second anodizing treatment, Figure 2 The thickness of the oxide layer 30 in the first porous layer 33 increases, and a portion of the pores 36 formed in the first porous layer 33 grows, and a portion (i.e., the second portion 313) having a larger pore diameter than the portion formed in the first anodizing treatment (i.e., the first portion 312) is formed at the front end thereof. Therefore, by performing the second anodizing treatment, as Figure 1 As shown, the second porous layer 34 can be formed between the barrier layer 32 and the first porous layer 33. In addition, Figure 2 The pores 36 in the second anodizing treatment that have not grown become Figure 1 The second fine hole 35 in.

[0057] The oxide layer 3 of the heat transfer member 1 in this example is provided with a plurality of pores 31 having a first portion 312 and a second portion 313. The pores 31 having such a shape promote the vaporization of the refrigerant when in contact with the superheated refrigerant, and can generate a large number of bubbles. In addition, the first portion 312 of the pores 31 has an opening 311 with a relatively small opening diameter, so that the grown bubbles can be quickly separated from the heat transfer member 1.

[0058] In addition, the average opening diameter of the first portion 312 of the pores 31 is smaller than the average pore diameter of the second portion 313, thereby suppressing the refrigerant in the liquid phase from entering the pores 31. Therefore, in the pores 31 of the heat transfer member 1, for example, even when the refrigerant is repeatedly boiled or immersed in the refrigerant for a long time, it is easy to retain gas in the pores 31. Furthermore, the gas in the pores 31 promotes the boiling of the refrigerant, thereby maintaining the effect of promoting the boiling of the refrigerant for a long time.

[0059] (Experimental example) In this example, the cooling performance of the heat transfer member having an oxide layer having various structures is described. It should be noted that among the symbols used in this experimental example, the same symbols as those used in the existing embodiments represent the same components as those in the existing embodiments unless otherwise specified.

[0060] like Figure 3 As shown, the heat transfer member 101 of this example has a cylindrical rod portion 11 and a fin portion 12 extending radially outward from a first end portion 111 of the rod portion 11. The diameter of the rod portion 11 is 30 mm, and the diameter of the fin portion 12 is 50 mm. The heat receiving surface 13 of the heat transfer member 101 is arranged at the second end portion 112 of the rod portion 11, that is, the end portion on the side without the fin portion 12. The heat dissipation surface 14 of the heat transfer member 101 is composed of the end surface on the side with the fin portion 12 in the heat transfer member 101, that is, the surface of the first end portion 111 of the rod portion 11 and the surface of the fin portion 12, and an oxide layer 3 having pores and second pores is provided on the heat dissipation surface 14. The base material 2 of the heat transfer member 101 is composed of an aluminum alloy having a chemical composition represented by the alloy number A5056.

[0061] The manufacturing method of the heat transfer component 101 of this example is as follows. First, the cylindrical base material 2 is subjected to cutting to form the rod portion 11 and the fin portion 12. Then, the surface of the base material 2 other than the heat dissipation surface 14 is covered with a protective material. In this state, the first anodizing treatment is performed by a constant voltage direct current electrolysis method. The type, concentration, bath temperature, applied voltage and voltage application time of the electrolyte in the first anodizing treatment are set to the values ​​shown in Table 1.

[0062] After the first anodizing treatment is completed, the second anodizing treatment is continuously performed. The electrolysis method in the second anodizing treatment is a constant voltage direct current electrolysis method. In addition, in the second anodizing treatment, the applied voltage is increased to the value shown in Table 1 after 2.5 minutes from the moment when the first anodizing treatment is completed, and the applied voltage is maintained. The type, concentration, bath temperature and voltage application time of the electrolyte in the electrolyte solution in the second anodizing treatment are set to the values ​​shown in Table 1.

[0063] Through the above, the test bodies S1 to S3 shown in Table 1 can be obtained. The oxide layer 3 provided on the heat dissipation surface 14 of the test bodies S1 to S3 has pores 31, and the pores 31 have a first portion 312 and a second portion 313 (see Figure 1 As an example, in Figure 4 2 shows an electron microscope image of the surface of the oxide layer 3 of the test body S1. Figure 4 The portion with a relatively bright contrast in FIG. 1 is the surface of the oxide layer 3 , and the portion with a relatively dark contrast is the opening 311 of the pore 31 or the opening 351 of the second pore 35 .

[0064] in addition, Figure 5 The electron microscope image of the cross section of the oxide layer 3 of the test body S1 is shown. Figure 5 The lower part is the base material 2, and the fracture surface of the oxide layer 3 is exposed on the base material 2. Figure 5As shown, near the surface of the oxide layer 3 , there are first portions 312 and second portions 35 of the pores 31 having relatively small pore diameters, and inside the oxide layer 3 , there is a second portion 313 having a pore diameter larger than the first portion 312 .

[0065] The average opening diameter of the first portion 312, the average depth of the first portion 312, the average pore diameter of the second portion 313, and the average depth of the second portion 313 of the pores 31 in the test bodies S1 to S3 are shown in Table 2. It should be noted that, as described above, the average opening diameter of the first portion 312 can be calculated based on the electron microscope image of the surface of the oxide layer 3. In addition, as described above, the average depth of the first portion 312, the average pore diameter of the second portion 313, and the average depth of the second portion 313 can be calculated based on the electron microscope image of the cross section of the oxide layer 3.

[0066] In addition, the test bodies R1 to R4 shown in Tables 1 and 2 are test bodies for comparison with the test bodies S1 to S3. The test bodies R1 to R2 have the same structure as the test bodies S1 to S3 except that the average opening diameter of the first portion 312 of the pores 31 is the value shown in Table 2. The manufacturing method of the test bodies R1 to R2 is the same as the manufacturing method of the test bodies S1 to S3 except that the processing conditions in the first anodizing treatment and the second anodizing treatment are changed as shown in Table 1.

[0067] When manufacturing the test body R3, after preparing the same base material as that used in the manufacture of the test bodies S1 to S3, the first anodizing treatment was performed by constant current direct current electrolysis. The heat transfer member thus obtained was set as the test body R3. The current density in the first anodizing treatment was 5 mA / cm 2 In addition, the type, concentration, bath temperature and current application time of the electrolyte in the first anodizing treatment are shown in Table 1. It should be noted that in the constant voltage direct current electrolysis method, the applied voltage can be changed, so the symbol "-" is recorded in the "applied voltage" column of Table 1. Figure 2 As shown in Table 2, the test piece R3 has the first porous layer 33 stacked on the barrier layer 32 and does not have the second porous layer 34. The average opening diameter of the pores 36 in the first porous layer 33 of the test piece R3 is as shown in Table 2.

[0068] The test piece R4 does not have the oxide layer 3 , and is composed only of the base material 2 .

[0069] The cooling performance of the heat transfer member 101 can be evaluated based on the thermal conductivity in the supercooled pool boiling experiment.

[0070] Figure 64 is an experimental device for supercooled pool boiling experiment. The experimental device 4 comprises: a heat insulating portion 41, which is made of a heat insulating material and is in a cylindrical shape; a refrigerant pool 42, which is arranged in the cylinder of the heat insulating portion 41; a heat source portion 43, which is arranged in the refrigerant pool 42 and heats the heat transfer member 101; and a vacuum pump 44, which is used to degas the refrigerant C in the refrigerant pool 42.

[0071] The refrigerant pool 42 comprises: a side wall portion 421, which is arranged opposite to the insulation portion 41; a top wall portion 422, which abuts against the upper end of the side wall portion 421 to constitute the top surface of the refrigerant pool 42; and a bottom wall portion 423, which abuts against the lower end of the side wall portion 421 to constitute the bottom surface of the refrigerant pool 42. The refrigerant pool 42 is constructed to be able to store the refrigerant C in the internal space surrounded by the side wall portion 421, the top wall portion 422 and the bottom wall portion 423.

[0072] A condenser 424, a thermocouple 425, an upper refrigerant heater 426, and a refrigerant cooler 427 are mounted on the top wall 422. The condenser 424 is configured to condense the vapor of the refrigerant C in the refrigerant pool 42 and return the refrigerant C in the liquid phase to the refrigerant pool 42. The thermocouple 425 is disposed through the top wall 422 and is configured to measure the temperature of the refrigerant C.

[0073] The upper refrigerant heater 426 and the refrigerant cooler 427 are disposed above the heat source unit 43. The upper refrigerant heater 426 and the refrigerant cooler 427 are connected to a temperature adjustment device (not shown) and are configured to adjust the temperature of the refrigerant C by heating or cooling the refrigerant C.

[0074] The heat source part 43 is arranged on the bottom wall part 423 of the refrigerant pool 42. The heat source part 43 has a shell 431 and a heater 432 arranged in the shell 431. The heater 432 is in the shape of a bottomed cylinder, and is configured to allow the rod part 11 of the heat transfer member 101 to be inserted. In addition, a heat insulating material 433 is sandwiched between the shell 431 and the heater 432. The heat insulating material 433 is arranged in a manner to cover the rod part 11 of the heat transfer member 101 and the heater 432. As a result, the heater 432 and the rod part 11 are thermally insulated from the surroundings of the heat source part 43.

[0075] The housing 431 has an opening 434 on its top surface. The fin portion 12 of the heat transfer member 101 is disposed in the opening 434 of the housing 431 .

[0076] In addition, a lower refrigerant heater 428 is mounted on the bottom wall portion 423. The lower refrigerant heater 428 is disposed around the heat source portion 43. The lower refrigerant heater 428 is connected to a temperature adjustment device (not shown) similarly to the upper refrigerant heater 426 and the refrigerant cooler 427, and is configured to be able to adjust the temperature of the refrigerant C by heating the refrigerant C.

[0077] The vacuum pump 44 is disposed outside the coolant pool 42 , and is connected to the coolant pool 42 via a pipe 441 attached to the top wall portion 422 and a vacuum valve 442 .

[0078] Next, the experimental method of the supercooled pool boiling experiment is described. First, a plurality of thermocouples 45 are installed at intervals in the length direction of the rod 11 of the fully dried heat transfer member 101. These thermocouples 45 are connected to a data processing device (not shown). The data processing device is configured to calculate the temperature of the heat dissipation surface 14 and the heat flux flowing from the heat dissipation surface 14 to the refrigerant C based on the temperature of the rod 11 measured by the thermocouples 45.

[0079] Next, a stainless steel ring (not shown) is installed on the outer periphery of the fin portion 12. Then, the rod portion 11 of the heat transfer member 101 is inserted into the heater 432, and the heat transfer member 101 is arranged in such a manner that the heat dissipation surface 14 is exposed from the opening 434 of the shell 431. Next, the refrigerant C is injected into the refrigerant pool 42 so that the height of the liquid level becomes 120 mm when the heat dissipation surface 14 is used as a reference. It should be noted that in this example, as the refrigerant C, either ethanol with a purity of 99.5% or hydrofluoroether ("Novec (registered trademark) HFE-7100" manufactured by 3M Company) is used.

[0080] Next, the refrigerant C is degassed according to the following steps. First, the temperature of the refrigerant C is raised to the saturation temperature by the upper refrigerant heater 426, the refrigerant cooler 427, and the lower refrigerant heater 428. Next, the heat transfer member 101 is heated by the heater 432 to boil the refrigerant C on the heat dissipation surface 14. After this state is maintained for 30 minutes, the heating by the heater 432 is stopped. Thereafter, the refrigerant pool 42 is depressurized by the vacuum pump 44 to degas the refrigerant C. Then, when the temperature of the thermocouple 45 closest to the heat dissipation surface 14 among the multiple thermocouples 45 installed on the heat transfer member 101 becomes lower than the saturation temperature of the refrigerant C, the degassing of the refrigerant C is completed, and the refrigerant pool 42 is returned to the atmospheric pressure. After the refrigerant pool 42 is pressurized to the atmospheric pressure, it is left to stand for 24 hours, thereby simulating the state in which the heat transfer member 101 is immersed in the refrigerant C for a long time.

[0081] After the preparation for the measurement is performed as described above, the temperature of the refrigerant C is raised to the saturation temperature again by the upper refrigerant heater 426, the refrigerant cooler 427, and the lower refrigerant heater 428. Then, 2 minutes after the temperature of the heat dissipation surface 14 and the refrigerant C reaches a stable state, the heater 432 starts heating the heat transfer member 101 to increase the heat input to the heat receiving surface 13 in stages. In addition, the heating of the heat transfer member 101 starts, and the measurement of the temperature of the rod 11 by the thermocouple 45 starts, and a boiling curve is prepared based on the result.

[0082] exist Figure 7 , as an example, boiling curves of test pieces S1 and R4 when hydrofluoroether (HFE) is used as the refrigerant C are shown. Figure 7 The horizontal axis in is the degree of superheat of the refrigerant C on the heat dissipation surface 14 (that is, the value obtained by subtracting the boiling point of the refrigerant C from the temperature of the heat dissipation surface 14). Figure 7 The vertical axis in is the average value of the heat flux value flowing from the heat dissipation surface 14 to the refrigerant C within 2 minutes from the time when the temperature of the heat transfer member 101 and the refrigerant C reaches a stable state. It should be noted that the point marked with the symbol B is the point where the non-boiling state changes to the boiling state as described later, so the temperature of the heat transfer member 101 and the refrigerant C changes before and after the start of boiling. Therefore, with regard to this point, the average value of the heat flux within 30 seconds before the start of boiling is shown.

[0083] In the case of the experiment conducted by the method of this example, if the heat input from the heating surface 13 begins to increase, the refrigerant C on the heat dissipation surface 14 performs heat exchange with the refrigerant C without boiling. In addition, the temperature of the refrigerant C on the heat dissipation surface 14 gradually rises due to the heat input from the heating surface 13, and the refrigerant C becomes superheated. Therefore, if Figure 7 As shown, the boiling curve from the start of the test to the boiling of the refrigerant C is a gently rising curve to the right.

[0084] If the temperature of the refrigerant C on the heat dissipation surface 14 further rises and the superheat degree of the refrigerant C reaches a certain point, the refrigerant C starts to boil. Figure 7 In FIG. 1 , the point where the refrigerant C changes from a non-boiling state to a boiling state is marked with a symbol B. After boiling begins, the refrigerant C takes heat from the heat transfer member 101 when it vaporizes, and the temperature of the heat dissipation surface 14 decreases, so the superheat of the heat dissipation surface 14 decreases temporarily. Furthermore, the amount of heat transferred from the heat transfer member 101 to the refrigerant C increases due to the vaporization of the refrigerant C, so the heat flux flowing from the heat dissipation surface 14 to the refrigerant C increases. Therefore, as Figure 7 As shown, the boiling curve from the time when the refrigerant C starts to boil (that is, the point indicated by the symbol B) to the time when the refrigerant C reaches a stable state is a curve that rises to the left.

[0085] Then, when the boiling of the refrigerant C reaches a steady state, the superheat rises and the value of the heat flux increases. Figure 7 As shown, the boiling curve of the refrigerant C becomes a rightward rising curve again after the boiling reaches a stable state. In addition, after boiling, the amount of heat transferred from the heat transfer member to the refrigerant increases due to the vaporization of the refrigerant, so the slope of the boiling curve after boiling is greater than the slope of the boiling curve before boiling.

[0086] exist Figure 7 In order to compare with the boiling curve of the heat transfer member 101, the solid line L represents the heat flux of nucleate boiling predicted based on the Rohsenow equation (the following equation (1)) when the heat dissipation surface 14 is assumed to be a smooth surface. p is the constant product specific heat [J kg -1 K -1 ], ΔT is the superheat [K], L lv is the latent heat of evaporation [J kg -1 ], q is the heat flux [W m -2 ], μ is the absolute viscosity [Pa s], σ is the surface tension [N m -1 ], ρ is the density of the liquid refrigerant C [kg m -3 ], ρ g is the vapor density of refrigerant C [kg m -3 ], k is the thermal conductivity of refrigerant C [W m -1 K -1 ]. In addition, C sf and n is a parameter that depends on the combination of the refrigerant C and the material of the heat transfer member 101. sf The value of was set to 0.0008 and the value of n was set to 1.18. These values ​​are quoted from the literature (ILPioro et al 1999).

[0087]

Mathematical formula 1

[0088] [Table 1] [Table 2] [Table 3] As shown in Table 3, the test pieces S1 to S3 having the pores 31 of the specific shape can boil the refrigerant C at a relatively low degree of superheat in both the case where ethanol is used as the refrigerant C and the case where HFE is used as the refrigerant C.

[0089] In contrast, the superheat at the start of boiling of the test bodies R1 to R2 having a short average depth of the second portion 313 of the pores 31 was higher than that of the test bodies S1 to S3. This is believed to be because the volume of the pores 31 in the test bodies R1 to R2 was small, and the amount of gas that could be retained in the pores 31 was insufficient, so the effect of promoting the boiling of the refrigerant C could not be obtained.

[0090] In addition, the superheat degree at the beginning of boiling of the test body R3 without a concave cavity was higher than that of the test bodies S1 to S3. This is believed to be because the pore diameter of the pores 31 provided in the oxide layer 3 of the test body R3 was relatively large over the entire length of the pores 31, and the liquid refrigerant C easily entered the pores 31 during the preparation of the test, and the gas could not be retained in the pores 31.

[0091] The superheat degree at the start of boiling of the test body R4 without the pores 31 was higher than that of the test bodies S1 to S3. This is probably because the effect of promoting boiling of the refrigerant C could not be obtained because there were no pores 31 capable of retaining gas on the surface of the test body.

[0092] In addition, if Figure 7 As shown, the slope of the boiling curve of the test body R4 without the pores 31 after the boiling of the refrigerant C reaches a stable state is lower than that of the test body S1, and the heat flux of the refrigerant C after boiling is smaller than that of the test body with the pores 31. Therefore, it can be understood from the comparison between the test bodies S1 and R4 that by providing the oxide layer 3 with the pores 31 on the heat dissipation surface 14 of the heat transfer member 101, the cooling performance of the refrigerant C after boiling can be significantly improved.

[0093] The above describes the specific aspects of the heat transfer component 101 and the manufacturing method thereof according to the present invention based on the embodiments and experimental examples. However, the heat transfer component 101 and the manufacturing method thereof according to the present invention are not limited to the embodiments and the experimental examples, and the structure can be appropriately changed within the scope that does not affect the main purpose of the present invention.

[0094] For example, one aspect of the present invention is a heat transfer member according to the following [1] to [5].

[0095] [1] A heat transfer member comprising: a base material composed of a metal or an inorganic compound containing a metal element; and an oxide layer composed of an oxide of a metal element contained in the base material and formed on the base material, The oxide layer has a plurality of pores, the plurality of pores comprising: a first portion having an opening on the surface of the heat transfer member, wherein the average opening diameter of the opening is greater than or equal to 5 nm and less than or equal to 70 nm; and a second portion having an average pore diameter greater than the average opening diameter of the first portion and connected to the first portion, The average depth of the second portion is 600 nm or more and 20 μ m or less.

[0096] [2] In the heat transfer member described in [1], the average pore diameter of the second portion is 70 nm or more and 1000 nm or less.

[0097] [3] The heat transfer member according to [1] or [2], wherein the average depth of the first portion is 100 nm or more and μ m or less.

[0098] [4] Regarding the heat transfer member described in any one of [1] to [3], the average depth of the second portion is at least 3 times the average depth of the first portion.

[0099] [5] Regarding the heat transfer member described in any one of [1] to [4], the base material is made of aluminum or an aluminum alloy.

[0100] Furthermore, another aspect of the present invention is a method for manufacturing a heat transfer member according to the following [6].

[0101] [6] A method for manufacturing a heat transfer member, which is the method for manufacturing a heat transfer member according to any one of [1] to [5], and comprises the following steps: By performing an anodic oxidation treatment on the base material under a first treatment condition, an oxide layer is formed on the surface of the base material, wherein the oxide layer has a plurality of pores having an average opening diameter of 5 nm or more and 70 nm or less; Then, the base material is anodized under a second treatment condition different from the first treatment condition to grow a part of the plurality of pores, thereby forming the second portion connected to the first portion.

Claims

1. A heat transfer component comprising: A base material composed of a metal or an inorganic compound containing a metal element; and an oxide layer composed of an oxide of a metal element contained in the base material and formed on the base material, The oxide layer has a plurality of pores, the plurality of pores comprising: a first portion having an opening on the surface of the heat transfer member, wherein the average opening diameter of the opening is greater than or equal to 5 nm and less than or equal to 70 nm; and a second portion having an average pore diameter greater than the average opening diameter of the first portion and connected to the first portion, The average depth of the second portion is 600 nm or more and 20 μ m or less.

2. The heat transfer member according to claim 1, wherein The average pore diameter of the second portion is 70 nm or more and 1000 nm or less.

3. The heat transfer member according to claim 1 or 2, wherein: The average depth of the first portion is greater than 100 nm and μ m or less.

4. The heat transfer member according to any one of claims 1 to 3, wherein The average depth of the second portion is more than 3 times the average depth of the first portion.

5. The heat transfer member according to any one of claims 1 to 4, wherein The base material is made of aluminum or an aluminum alloy.

6. A method for manufacturing a heat transfer member, which is the method for manufacturing a heat transfer member according to any one of claims 1 to 5, and comprises the following steps: By performing an anodic oxidation treatment on the base material under a first treatment condition, an oxide layer is formed on the surface of the base material, wherein the oxide layer has a plurality of pores having an average opening diameter of 5 nm or more and 70 nm or less; Then, the base material is anodized under a second treatment condition different from the first treatment condition to grow a part of the plurality of pores, thereby forming the second portion connected to the first portion.

Citation Information

Patent Citations

  • Heat transfer promoting method and boiling heat transfer

    JP2002228389A